“It Is a Total Drama”: Land Use Conflicts in Local Land Use Actors’ Experience - Meike Fienitz; Rosemarie Siebert (Land, 2022)
As land is limited, conflicts between land uses, and, consequently, conflicts between land users about land use inevitably arise. However, how these land use conflicts affect local land use actors has remained underexplored. The objective of this paper is to provide a broad, cross-sectoral overview of land use conflicts as perceived by local land use actors and to explore the actors’ experiences with these conflicts. We conducted 32 semistructured interviews with key land use actors (mayors, local agencies, interest groups, local boards, businesses) in the urban-rural fringe region of Schwerin, Germany. We then applied a qualitative text analysis to identify the region’s most relevant conflicts across all land use sectors (agriculture, settlement, infrastructure, forestry, conservation, tourism, industry, etc.) and their impacts on local actors’ daily experiences. The results show that local actors are aware of many diverse land use conflicts, most frequently regarding land uses for housing, environmental/species conservation, and traffic. Moreover, local actors report these conflicts as relevant to their daily work, and many perceive the conflicts as a strain. Conflicts impede land management processes; they tie up resources, are often perceived as complex, and can be experienced as highly stressful—as summed up in an interviewee’s conclusion: “It is a total drama”. Thus, land use conflicts play an important and mostly negative role in the experiences of land use actors. These findings fill current gaps in the literature on land use conflicts regarding the types of conflicts about which actors are aware and the consequences of these conflicts. The results also underline the relevance of addressing conflicts in land use planning and governance, the need for appropriate conflict management, and the necessity of providing local actors with sufficient resources to deal with land use conflicts. The paper further identifies some starting points so conflicts can enhance rather than impede communal life in rural areas.